2015
DOI: 10.1002/2014ja020773
|View full text |Cite
|
Sign up to set email alerts
|

The equatorial electrojet during geomagnetic storms and substorms

Abstract: The climatology of the equatorial electrojet during periods of enhanced geomagnetic activity is examined using long‐term records of ground‐based magnetometers in the Indian and Peruvian regions. Equatorial electrojet perturbations due to geomagnetic storms and substorms are evaluated using the disturbance storm time (Dst) index and auroral electrojet (AE) index, respectively. The response of the equatorial electrojet to rapid changes in the AE index indicates effects of both prompt penetration electric field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 48 publications
9
56
0
Order By: Relevance
“…Third plot is the cross correlation of IMF-Bz with SYM-H, Utot, Ua, Ur, and Uj quantifying the response of the solar wind invasion in the magnetosphere. This observation is similar to the summary of substorm analysis of Yamazaki and Kosch (2015) where AE was showing abrupt response at least of every 3-4 hr. The correlation curve near the value zero shows the weaker correlation whereas the curve near the region of +1 or −1 represents higher correlation (Katz, 1988).…”
Section: Resultssupporting
confidence: 86%
“…Third plot is the cross correlation of IMF-Bz with SYM-H, Utot, Ua, Ur, and Uj quantifying the response of the solar wind invasion in the magnetosphere. This observation is similar to the summary of substorm analysis of Yamazaki and Kosch (2015) where AE was showing abrupt response at least of every 3-4 hr. The correlation curve near the value zero shows the weaker correlation whereas the curve near the region of +1 or −1 represents higher correlation (Katz, 1988).…”
Section: Resultssupporting
confidence: 86%
“…The observed ∆H decrease almost 10 hrs after the commencement of main phase makes disturbance dynamo effect a possible contributor to the westward electric field during 1100-1300 UT (0600-0800 LT). Numerical and observational investigations have indicated that the disturbance dynamo electric field can last hours to a day after the ceasing of high latitude activity/maximum geomagnetic activity [Huang et al, 2005;Yamazaki and Kosch, 2015]. The downward vertical drift observed in magnetometer data There should be a source of eastward electric field leading to enhanced vertical drifts which could later drive the observed TIDs.…”
Section: Resultsmentioning
confidence: 98%
“…Yamazaki and Kosch [] reported that the EEJ shows a different after storm response between the Indian and Peruvian sectors. They found a depression of the EEJ at Trivandrum (77°E) during afternoon hours but a little effect or even enhancement of the EEJ at Huancayo (285°E) within that local time sector.…”
Section: Discussionmentioning
confidence: 99%